2015
DOI: 10.1371/journal.pone.0124371
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs and their Targets Associated with Embryo Abortion during Chrysanthemum Cross Breeding via High-Throughput Sequencing

Abstract: BackgroundMicroRNAs (miRNAs) are important regulators in plant development. They post-transcriptionally regulate gene expression during various biological and metabolic processes by binding to the 3’-untranslated region of target mRNAs to facilitate mRNA degradation or inhibit translation. Chrysanthemum (Chrysanthemum morifolium) is one of the most important ornamental flowers with increasing demand each year. However, embryo abortion is the main reason for chrysanthemum cross breeding failure. To date, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 70 publications
1
12
0
1
Order By: Relevance
“…The number of sRNAs was far less than the report of miRNAs responsive to Botrytis cinerea in P. lactiflora 21, which demonstrated that the mechanism of colour formation was less complicated compared with the stress response in P. lactiflora . With respect to the length distribution of sRNAs, 21–24 nt sRNAs dominated the sRNA transcriptome in red outer-petal and yellow inner-petal with the 21-nt sRNAs being the most abundant in length, which was in accordance with the reports in P. lactiflora 21, P. persica 17 and C. indica 22, while not in agreement with 24-nt sRNAs being the most abundant in C. tinctorius 16 and D. morifolium 20. This was mainly because of the plant species and the specific enzymes that were used to process the different length of sRNAs40.…”
Section: Discussionsupporting
confidence: 60%
“…The number of sRNAs was far less than the report of miRNAs responsive to Botrytis cinerea in P. lactiflora 21, which demonstrated that the mechanism of colour formation was less complicated compared with the stress response in P. lactiflora . With respect to the length distribution of sRNAs, 21–24 nt sRNAs dominated the sRNA transcriptome in red outer-petal and yellow inner-petal with the 21-nt sRNAs being the most abundant in length, which was in accordance with the reports in P. lactiflora 21, P. persica 17 and C. indica 22, while not in agreement with 24-nt sRNAs being the most abundant in C. tinctorius 16 and D. morifolium 20. This was mainly because of the plant species and the specific enzymes that were used to process the different length of sRNAs40.…”
Section: Discussionsupporting
confidence: 60%
“…In chrysanthemum cross breeding, embryonic development is a crucial stage for seed formation, but embryo abortion is prevalent in chrysanthemum distant hybridization [ 31 , 32 ]. Previous studies explored this barrier at the level of cell structure, gene expression, and miRNA regulation [ 19 , 24 ], in which 227 miRNAs were identified in hybrid embryos from cross C. morifolium and diploid C. nankingense . Because of the importance of chromosome doubling in cross breeding, in the present study, we performed the hybridization using C. morifolium and tetraploid C. nankingense ; 179 miRNAs were identified in three embryo samples (Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA samples used for sequencing were reverse transcribed using PrimeScript miRNA qPCR starter kit ver 2.0 (Takara Bio, Dalian, China). qRT-PCR was performed using the SYBR Premix EX Taq Kit (Takara, Dalian, China), and the PCR amplification was done as described by Zhang et al [ 24 ]. Three biological replicates were performed for each sample, and relative expression levels were calculated by the 2 −△△CT method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…특히 miRNA의 target mRNA가 대부분이 전사조절인 자로 하위유전자의 발현에도 영향을 주기 때문에 그 영향 력이 매우 커서 국화에서도 NGS를 활용하여 miRNA가 전 게놈 수준에서 분석되었다 (Xia et al 2015;Zhang et al 2015). 원연교잡 후에 확보된 3종류의 배에서 228개의 miRNA가 동정되었으며, 각각의 배에서 특이적으로 발현되는 miRNA 도 규명되었다 .…”
Section: 장일(Long-day) 처리 중인 영양생장점(Vegetative Buds) 단일 을 시작한 후 화아분화가 unclassified